2018
DOI: 10.1002/ece3.3938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal foraging habitat on offspring quality in the loggerhead sea turtle (Caretta caretta)

Abstract: Exploring a trade‐off between quantity and quality of offspring allows differences in the fitness between alternative life histories to be accurately evaluated. We addressed the mechanism that maintains alternative life histories (small oceanic planktivores vs. large neritic benthivores) observed in a loggerhead sea turtle (Caretta caretta) population, which has been suggested to be environmental, based on the lack of genetic structure and a large difference in reproductive output. We examined whether maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…These results suggested that the proportion of nests damaged Maehama Inakahama Total 1 2 3 4 5 6 Total Oceanic 15 23 38 6 9 3 3 15 2 38 Neritic 136 352 488 64 72 55 82 204 11 488 or lost by natural causes (e.g., inundation, beach erosion) is similar for oceanic and neritic foragers. When taken together with the comparable quality (morphology, emergence success and activity levels) of hatchlings derived from the two foragers (Hatase et al, 2013(Hatase et al, , 2018, our results indicated that the survival rate of offspring on land is very similar between the two foragers. Thus, the 2.5-fold lower fecundity of oceanic foragers is unlikely to be offset by differences in offspring survival due to differential nest site selection.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These results suggested that the proportion of nests damaged Maehama Inakahama Total 1 2 3 4 5 6 Total Oceanic 15 23 38 6 9 3 3 15 2 38 Neritic 136 352 488 64 72 55 82 204 11 488 or lost by natural causes (e.g., inundation, beach erosion) is similar for oceanic and neritic foragers. When taken together with the comparable quality (morphology, emergence success and activity levels) of hatchlings derived from the two foragers (Hatase et al, 2013(Hatase et al, , 2018, our results indicated that the survival rate of offspring on land is very similar between the two foragers. Thus, the 2.5-fold lower fecundity of oceanic foragers is unlikely to be offset by differences in offspring survival due to differential nest site selection.…”
Section: Discussionmentioning
confidence: 67%
“…d 13 C and d 15 N were expressed as deviations from the standard, as defined by the following equation: d 13 C or d 15 N = (R sample /R standard -1) 9 1000 (&), where R is 13 C/ 12 C or 15 N/ 14 N. Vienna Pee Dee Belemnite (VPDB) and atmospheric nitrogen were used as the carbon and nitrogen isotope standards, respectively. Analytical precision was ≤0.15& for both d 13 C and d 15 N. Females producing yolks with a d 13 C of <-18.0& and a d 15 N of <12.0& were classified as oceanic planktivores, and females with a d 13 C of ≥-18.0& or a d 15 N of ≥12.0& were classified as neritic benthivores (Watanabe et al, 2011;Hatase et al, 2013Hatase et al, , 2018 following the findings of a previous study in which stable isotope analysis and satellite telemetry were simultaneously conducted on the same females and isotope ratios were compared between potential prey and females (Hatase et al, 2002b). To justify this method of classification, linear discriminant analysis was also conducted (see electronic supplementary material: Appendix S1).…”
Section: Measurements Of Stable Isotope Ratios and Classification Intmentioning
confidence: 99%
“…The compelling finding of apparent fitness differences between foraging groups (Hatase et al, ) raises the further question of whether a trade‐off exists that balances fitness between the two strategies, therefore maintaining both within a single population. To address this question numerous traits including age (Hatase et al, ), egg size & components (Hatase, Omuta & Komatsu, ), hatchling size (Hatase, Omuta & Komatsu, ) and various traits presumed to be indicative of offspring quality (Hatase et al, ) have been investigated that might contribute to such a trade‐off. None of these studies revealed a fitness trade‐off.…”
Section: Resultsmentioning
confidence: 99%
“…Eggs laid by a total of 531 females were collected for stable isotope analysis: 105 females from 22 May to 11 June 1999, 102 females from 15 May to 14 June 2008, 155 females from 17 to 25 May 2011, 20 females from 15 to 24 May 2013, 31 females from 22 May to 5 June 2014, 20 females from 25 June to 4 July 2015, 20 females from 4 to 9 July 2016 and 78 females from 12 May to 20 July 2017 (Hatase et al ., 2013, 2018; Hatase & Omuta, 2018). At our study site, there were fewer small oceanic foraging loggerheads than large neritic foragers (1:4 ratio), probably due to shorter remigration intervals and higher breeding frequency for large neritic foragers (Hatase et al ., 2013).…”
Section: Methodsmentioning
confidence: 99%
“…At our study site, there were fewer small oceanic foraging loggerheads than large neritic foragers (1:4 ratio), probably due to shorter remigration intervals and higher breeding frequency for large neritic foragers (Hatase et al ., 2013). For this reason, small females with a straight carapace length and width of <810 mm and <633 mm, respectively, and large females with a straight carapace length and width of ≥810 mm and ≥630 mm were selected during the 2013–2016 period (Hatase et al ., 2018). These criteria allowed us to obtain similar sample sizes of both small oceanic and large neritic foragers, classified by stable isotope ratios.…”
Section: Methodsmentioning
confidence: 99%